2018
DOI: 10.1101/485136
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Single-cell Transcriptomics reveals multi-step adaptations to endocrine therapy

Abstract: Resistant tumours are thought to arise from the action of Darwinian selection on genetically heterogenous cancer cell populations. However, simple clonal selection is inadequate to describe the late relapses often characterising luminal breast cancers treated with endocrine therapy (ET), suggesting a more complex interplay between genetic and non-genetic factors. Partially, this is due to our limited understanding on the effect of ET at the single cell level. In the present study, we dissect the contributions … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
65
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(69 citation statements)
references
References 62 publications
4
65
0
Order By: Relevance
“…We examined genetic heterogeneity in cell lines using CNA inferred from scRNA-seq, a method described in multiple previous studies 18,29 . To test robustness and accuracy of this method, we incorporated two external 10X scRNA-seq datasets, which investigated the same cell lines (MCF7 and T47D cells cultured in standard media 29 , plus three different MCF7 strains 21 ). Different strains of the same cell type exhibited high resemblance to each other, as shown by coclustering of T47D CDH1 WT and KO cells with the external T47D dataset ( Fig.…”
Section: Inferred Copy Number Aberrations (Cnas) Reveal Intra-cell LImentioning
confidence: 99%
“…We examined genetic heterogeneity in cell lines using CNA inferred from scRNA-seq, a method described in multiple previous studies 18,29 . To test robustness and accuracy of this method, we incorporated two external 10X scRNA-seq datasets, which investigated the same cell lines (MCF7 and T47D cells cultured in standard media 29 , plus three different MCF7 strains 21 ). Different strains of the same cell type exhibited high resemblance to each other, as shown by coclustering of T47D CDH1 WT and KO cells with the external T47D dataset ( Fig.…”
Section: Inferred Copy Number Aberrations (Cnas) Reveal Intra-cell LImentioning
confidence: 99%
“…The genetic characterisation of enriched CTCs could exhibit the global molecular portrait of the metastatic microenvironment [ 11 , 12 , 13 , 14 ]. However, it is unlikely to reveal the role of individual cancer cells due to the presence of other contaminated blood cells [ 1 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Besides, single-cell analysis requires a highly sensitive workflow to isolate the single CTCs from millions of lymphocytes and subsequent downstream experiments. Previous studies have shown that genetic profiles of single CTCs could display a comprehensive landscape of the molecular aberrations in the different signalling pathways and pinpoint new therapeutic targets [ 11 , 12 , 14 ]. Moreover, single-cell analysis of CTCs can exhibit discrepancies in the gene expression in different patients and within individual patient.…”
Section: Introductionmentioning
confidence: 99%
“…They can also evolve into new subclones which transform the original sensitive group into a resistant colony after treatment. 76 This also provides an explanation for the emergence of novel subclones carrying KRAS mutations in liver metastases from wild-type RAS CRC patients treated with chemotherapy. 7 Apart from providing more resistant subclones by heterogeneous tumors in the face of selection, the interaction between subclones will also lead to stronger drug resistance.…”
Section: F I G U R Ementioning
confidence: 92%